Pipevine Swallowtail, Blue Swallowtail Battus philenor (Linnaeus 1771) (Insecta: Lepidoptera: Papilionidae: Papilioninae: Troidini) - Donald W. Hall (EDIS, 2017)
This document provides an in-depth profile of the pipevine swallowtail butterfly, Battus philenor. It covers the butterfly’s nomenclature, distribution, physical description, life cycle, host plants, natural enemies, and defenses. The article also discusses the butterfly’s mimicry, pollination biology, and the ecological significance of its interactions with host plants and predators. The information is intended for both laypersons with some biological knowledge and academic audiences.